An Insight to Illness Narrated by A Patient with Right Hemisphere Damage Associated with Frontal Blood Flow Changes: An Implication for Self-Treatment of Lifestyle-Related Diseases - Takada, Junko; Meguro, Kenichi; Kinomura, Shigeo; Yamaguchi, Satoshi (Archives of Clinical and Medical Case Reports, 2020)
The authors experienced a case (Mr. T) with right hemisphere infarction. After he came to understand his disease, he changed his behavior; he reflected on his past conduct, had the consciousness to face his disease, improved his daily life. He talked about his past behavior as the cause of cognitive impairment. Mr. T reviewed his past behaviors before the hospital visit, saying “I can fully understand the way I am by considering my disease and myself separately.” Furthermore, as his living activities changed, the right frontal cerebral blood flow also improved. Early diagnosis is not necessarily accepted negatively by patients and their family. When an early diagnosis is made with an explanation of the disease, the patient may reflect on their past conduct, leading to changes in their living activities. In our case, it was fortunate that there were no problems. <gdiv></gdiv>